The sum of three consecutive even integers is 36. Let x represent the first integer, x + 2 represent the second integer, and x + 4 represent the third integer.

Which equation can be used to find the first integer?



Responses

3x + 6 = 36
3 x + 6 = 36

3x + 36 = 2x + 6
3 x + 36 = 2 x + 6

2x + 6 = 36
2 x + 6 = 36

3x = 2x + 6

1 answer

To find the equation that represents the sum of three consecutive even integers where the first integer is \( x \), the second integer is \( x + 2 \), and the third integer is \( x + 4 \), you can set up the equation as follows:

\[ x + (x + 2) + (x + 4) = 36 \]

This simplifies to:

\[ 3x + 6 = 36 \]

Thus, the correct equation that can be used to find the first integer is:

3x + 6 = 36